letters to the editor. - Hewitt, Carl; Genkin, Daniel; Pachmanov, Lev; Pipman, Itamar; Shamir, Adi; Tromer, Eran; Dunlavey, Michael R.; Gregg, Brendan; Humelsine, Jim (Communications of the ACM, 2016)
Letters to the editor are presented in response to articles in the June 2016 issue including "Physical Key Extraction Attacks on PCs" by Daniel Genkin et al., "The Flame Graph" by Brendan Gregg, and "Improving API Usability" by Brad A. Myers and Jeffrey Stylos.